Growth and nutritional quality in giant freshwater prawn, Macrobrachium rosenbergii through live mealworm feeding with probiotic enrichment - Sashwinie Murali,; Teoh, Chaiw-Yee; Wong, Wey-Lim (Penerbit Universiti Kebangsaan Malaysia, 2025)
To address the gap in sustainable aquaculture, a 17-week feeding trial was conducted to evaluate locally-sourced mealworms, with and without Bacillus subtilis probiotic enrichment, as an alternative feed material for giant freshwater prawn (Macrobrachium rosenbergii), assessing their effects on growth, feed utilization, and nutritional composition. Five experimental diets were tested: commercial prawn feed (CPF), CPF combined with live mealworm (CPF+MW), mealworm alone (MW), probiotic-enriched mealworm (PMW), and CPF combined with probiotic-enriched mealworm (CPF+PMW). Triplicate groups of 20 prawns were randomly assigned to each diet. Weight gain among the groups ranged from 421.88% to 529.34%, with no significant differences observed (P > 0.05). Prawns fed CPF exhibited a significantly higher feed conversion ratio (FCR) (3.72 ± 0.32, P < 0.05), indicating less efficient feed utilization and leading to increased production costs. While CPF (45.01%) and MW (52.44%) diets differed significantly in crude protein content, the prawns fed CPF (59.24%) and MW (60.78%) showed similar crude protein levels. These results suggest that live mealworms are a viable alternative to commercial feed for GFP, maintaining growth performance and nutritional quality. Furthermore, combining live mealworms with commercial feed proves to be an effective feeding strategy, though enrichment with B. subtilis did not provide additional benefits for prawn growth or FCR.